Pharmacotherapy of Traumatic Childhood Aphasia: Beneficial Effects of Donepezil Alone and Combined With Intensive Naming Therapy - Dávila, Guadalupe; Moyano, María Pilar; Edelkraut, Lisa; Moreno-Campos, Lorena; Berthier, Marcelo L.; Torres-Prioris, María José; López-Barroso, Diana (Frontiers in Pharmacology, 2020)
At present, language therapy is the only available treatment for childhood aphasia (CA). Studying new interventions to augment and hasten the benefits provided by language therapy in children is strongly needed. CA frequently emerges as a consequence of traumatic brain injury and, as in the case of adults, it may be associated with dysfunctional activity of neurotransmitter systems. The use of cognitive-enhancing drugs, alone or combined with aphasia therapy, promote improvement of language deficits in aphasic adults. In this study we report the case of a 9-year-old right-handed girl, subject P, who had chronic anomic aphasia associated with traumatic lesions in the left temporal-parietal cortex. We performed a single-subject, open-label study encompassing administration of the cholinergic agent donepezil (DP) alone during 12 weeks, followed by a combination of DP and intensive naming therapy (INT) for 2 weeks and thereafter by a continued treatment with DP alone during 12 weeks, a 4-week washout period, and another 2 weeks of INT. Four comprehensive language and neuropsychological evaluations (LNE) were performed at different timepoints along the study, and structural magnetic resonance (MRI) imaging was performed at baseline. Baseline MRI revealed two focal lesions, one large involving the posterior inferior and middle temporal gyri and another comprising the angular gyrus in the left hemisphere. Overall, baseline evaluation disclosed marked impairment in naming, spontaneous speech, repetition, auditory comprehension and executive and attention functions, while memory and visuoconstructive and visuoperceptive functions were preserved. Treatment with DP alone significantly improved spontaneous speech, auditory comprehension, repetition and picture naming. Additionally, treatment with DP alone improved processing speed, selective and sustained attention. Combined DP-INT further improved naming. After washout of both interventions, most of these beneficial changes remained. Importantly, there were no side effects to the drug treatment and subject P attained the necessary level of language skills to return to regular schooling. In conclusion, the use of DP alone and in combination with INT improved language function and related cognitive posttraumatic deficits in a child with acquired aphasia. Further studies in larger samples are warranted.